PENGARUHSTORE ENVIRONMENT DAN IN STORE PROMOTION TERHADAP IMPULSE BUYING MELALUI EMOSI POSITIF(STUDI PADA KONSUMEN RAMAYANA DEPT STORE SALATIGA) - Nurlan Oktafiani Siregar; Naili Farida; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2015)
The research was conducted due to the target selling in Ramayana Departement Store Salatiga  has  been undera achived since the last three years. This matter was giving signs that Store Environment and in Store Promotion in Ramayana Departement Store Salatiga has been failed to attract the consumers of buying their goods. The purpose of this research were to determine the influence of store environment and in store promotion on positive emotion and impulse buying behavior. The Sampling Method used in this research was actidental sampling and purposed sampling on 100 respondents. This research was also using path analysis technique supported by SPSS 16.0 version. The validity test, reliability test, correlation coefficient test, linear and multiple regression, coefficient of determination test, and signification test (F and T test) with Sobel method beforehand. The result has shown that the direct influence regarding the  store environment and in store promotion on positive emotion and impulse buying, and positive emotion on impulse buying andproven the indirect influence between store environment and in store promotion on impulse buying mediated customers positif emotion.